Regulation of hepatic TRB3/Akt interaction induced by physical exercise and its effect on the hepatic glucose production in an insulin resistance state - Marinho, Rodolfo [UNESP]; Mekary, Rania A.; Muñoz, Vitor Rosetto; Gomes, Ricardo José; Pauli, José Rodrigo [UNESP]; Moura, Leandro Pereira de [UNESP] (Springer Nature, 2015)
To maintain euglycemia in healthy organisms, hepatic glucose production is increased during fasting and decreased during the postprandial period. This whole process is supported by insulin levels. These responses are associated with the insulin signaling pathway and the reduction in the activity of key gluconeogenic enzymes, resulting in a decrease of hepatic glucose production. On the other hand, defects in the liver insulin signaling pathway might promote inadequate suppression of gluconeogenesis, leading to hyperglycemia during fasting and after meals. The hepatocyte nuclear factor 4, the transcription cofactor PGC1-α, and the transcription factor Foxo1 have fundamental roles in regulating gluconeogenesis. The loss of insulin action is associated with the production of pro-inflammatory biomolecules in obesity conditions. Among the molecular mechanisms involved, we emphasize in this review the participation of TRB3 protein (a mammalian homolog of Drosophila tribbles), which is able to inhibit Akt activity and, thereby, maintain Foxo1 activity in the nucleus of hepatocytes, inducing hyperglycemia. In contrast, physical exercise has been shown as an important tool to reduce insulin resistance in the liver by reducing the inflammatory process, including the inhibition of TRB3 and, therefore, suppressing gluconeogenesis. The understanding of these new mechanisms by which physical exercise regulates glucose homeostasis has critical importance for the understanding and prevention of diabetes.
Keywords: Hepatic glucose production; Insulin resistance; Liver; Physical exercise; Trb3